Obtaining immunodiagnostic preparations from Toxocara canis antigens for serodiagnostics of toxocariasis in human - Irina V. Kanina; A. I. Novak; M. D. Novak; O. V. Evdokimova (Инфекция и иммунитет, 2022)
Toxocariasis is a human helminthic invasion that has a wide range of hosts with epizootic distribution. The populational seropositivity in countries with a temperate climate comprises about 37%, whereas in regions with tropical climate up to 92%. Almost all age groups of the population are at risk of invasion by toxocars. The immunological method currently retains diagnostic significance for toxocariasis, because the reaction of immune system against helminths is accompanied by developing sensitization, and techniques as well as methods of collecting clinical material to identify the migratory form of toxocarosis in humans are time-consuming and invasive. The purpose of this study is to develop an immunobiological preparation based on excretory-secretory antigens from Toxocara canis larvae for serodiagnostics of larva migrans syndrome in human by using enzyme-linked immunoassay (ELISA). Antigens were obtained from Toxocara canis larvae by culturing its eggs isolated from the uterus of female nematodes in the glutamine-supplemented medium. The preparation was purified from ballast substances by centrifugation at 8000 g for 20 minutes followed by filtration through microfiltration membrane with a pore diameter of 0,050,15 microns, type MFAS-P-1 (manufactured by CJSC STC Vladipor). Blood serum of student volunteers from countries with high incidence rate of toxocariasis were tested to detect T. canis-specific antibodies. ELISA with commercial antigens Toxocara-IgG-ELISA-BEST kit was used for selection of seropositive and seronegative sera also used as a control. Diagnostic antigenic preparations with different protein concentrations were prepared to examine seropositive sera for determining optimal dose of the antigenic drugs. Results. ELISA with standard test kit allowed to detect Toxocara-IgG antibodies in 20 sera (8%) from 250 samples, what indicates about antigenic stimulation of the immune system by helminths and suspected former disease. Analyzing experimental samples allowed to find the number of seropositive data correlated with antigenic protein concentration in preparations: at a concentration of 1,96 g/ml 5,2% of positive results were detected, 1,71 g/ml 3.2%, 0.33 g/ml 0.8% (Pearsons correlation coefficient 0,94). The number of positive sera detected with commercial antigen in ELISA kit was identical to that of positive sera detected by an experimental antigen sample with a protein concentration of 2,49 g/ml. Thus, the immunodiagnostic preparations obtained by the experimental method based on the excretory-secretory antigens from Toxocara canis are characterized by high sensitivity and can be used to detect Toxocara-IgG antibodies in ELISA. The antigen preparation protein concentration of at least 2.49 g/ml is optimal and correlates whit sensitivity of the commercial antigen of the standard ELISA.